Efficiency of Provincial Healthcare Systems in 2017-2022 Before and During the COVID-19 Pandemic - Biernacki, Marek (Efektywność wojewódzkich systemów opieki zdrowotnej w latach 2017-2022 przed pandemią COVID-19 i w jej trakcie, 2024)
The article aims to assess the efficiency of provincial healthcare systems in relation to the macroregion in which a given province is located and with regard to the entire country. During the analysed period of 2017-2022, encompassing both the time before and during the COVID-19 pandemic, increases in expenditures on provincial healthcare systems did not result in the expected improvements in health indicators. The healthcare systems of wealthier provinces demonstrated decreased efficiency during the pandemic compared to poorer regions within their respective macroregions and across the entire country. Before the pandemic, the red macroregion performed slightly better than the green and yellow macroregions. During the pandemic, the green macroregion was the most efficient, while in the second year of the pandemic, the red macroregion became the least efficient.
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2024, Nr 22 (28), s. 13-20
Keywords: efficiency; healthcare systems; Data Envelopment Analysis; Non-Profit Efficiency; wydajność; system ochrony zdrowia; analiza otoczki danych; efektywność instytucji non-profit